2021
DOI: 10.3389/fpsyg.2021.658739
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Analysis of Spiritual Bypass: A Comparison Between Spain and Honduras

Abstract: Religion and spirituality (R/S) serve as coping mechanisms for circumstances that threaten people’s psychological well-being. However, using R/S inappropriately to deal with difficulties and problems in daily life may include the practice of Spiritual Bypass (SB). SB refers to avoiding addressing emotional problems and trauma, rather than healing and learning from them. On the other hand, coping strategies may be determined by the cultural context. This study aims to describe the presence of SB in individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…It can be inferred from this result that using negative coping strategies risks people s perception of happiness and their own social support systems. In this study we did not study the effect of using religious practices to hide feelings (spiritual bypassing), but this particular finding might be related to it (Motiño et al 2021). Finally, it was found that positive religious coping mechanisms are greater in people whose religiosity is higher.…”
Section: Discussionmentioning
confidence: 87%
“…It can be inferred from this result that using negative coping strategies risks people s perception of happiness and their own social support systems. In this study we did not study the effect of using religious practices to hide feelings (spiritual bypassing), but this particular finding might be related to it (Motiño et al 2021). Finally, it was found that positive religious coping mechanisms are greater in people whose religiosity is higher.…”
Section: Discussionmentioning
confidence: 87%
“…Even in the specific case of cancer, the religious/spiritual struggle was associated with greater symptom burden and poorer quality of life [ 90 ], as well as greater depression [ 91 ]. At this point, it is worth noting that there are other religious/spiritual constructs that, as in the case of spiritual struggles, have a negative impact on people’s psychological well-being, such as spiritual bypass [ 13 ] or guilt [ 92 ]. In any case, more research is needed on the serious consequences that mistrust in God may have on people’s health.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in Spain, interest in the field is not as broad, although there are researchers that have studied R/S in relation to various aspects of mental health [ 12 , 13 ], health behaviors [ 14 ] or physical health [ 15 , 16 ] in the Spanish context. The paucity of literature on these relationships in the context of this country may be surprising, given the deep-rooted Christian Catholic culture in Spain, whose values in many cases are closely related to health care.…”
Section: Introductionmentioning
confidence: 99%
“…The SBS-13 consists of two factors, Spiritualizing (i.e., overappraisals of difficulties as stemming from spiritual origins) and Psychological Avoidance (i.e., avoiding difficult emotions and experiences using spiritual means), that load onto a higher order factor of Spiritual Bypass. Studies have explored the factor structure (and/or translations) of the SBS-13 in Brazil (Picciotto et al, 2018), India (Toussaint et al, 2021), Spain, Honduras (Motiño et al, 2021), and a mixture of Korean Americans and Koreans living in Korea (Taylor et al, 2021). Results revealed that the psychometric properties of the SBS-13 are retained well across cultures, although an item (usually the reverse-coded Item 1) is often excluded due to a negative loading, errors in translation (Motiño et al, 2021; Picciotto et al, 2018) or a lack of fit (Taylor et al, 2021).…”
Section: Religious and Spiritual (R/s) Coping In Muslimsmentioning
confidence: 99%